USAHA LOLOH KUNYIT KOMUNITAS KOLOK BERBASIS POTENSI LOKAL DI DESA BENGKALA, BULELENG, BALI - Ni Wayan Arini; Dewa Bagus Sanjaya; Dewa Nyoman Sudana (Ngayah: Majalah Aplikasi IPTEKS, 2019)
The aim of this activity was to empower the kolok community through making local turmeric loloh based on the potential in Bengkala Village. Kolok community development is carried out with the guidance of Competency Standards (SK) and Basic Competencies (KD), then translated into the Learning Implementation Plan (RPP) skills. This empowerment activity has multiple benefits, namely complete illiteracy, and independent business skills. As a kolok community independent business with the technical implementation as follows. (1) Expressing the desire to try the kolok community based on their interests and potential, (2) Practicing a skill that has the opportunity to become a business field in accordance with available local interests and potential. The approach used in this activity is a pedagogical, functional, and thematic approach. The methods used in learning activities are lectures, discussions, and direct practice. The results of the activity showed that the kolok community had hygienic skills and variety in taste. Besides skills, it also adds income, and completes independent business literacy (KUM).